The Effect of Hot Extrusion on Mechanical and Tribological Behavior of Ag-Cu/MoS2 Composites. Issue 2 (3rd March 2016) - Chen, Wu; Wang, Yan; Zhang, Lei; Feng, Chunfang; Zhou, Kechao
ABSTRACT: Silver–copper/molybdenum disulfide (Ag-Cu/MoS2 ) composites, prepared by powder metallurgy and hot press sintering, were extruded at a temperature of 680°C with extrusion ratios of 10 and 70. Mechanical tests and tribotests were carried on both the hot-pressed and hot-extruded composites. The tribological properties of the composites against a silver coin disc were investigated on a pin-on-disc tester with normal load and sliding speed of 5 N and 0.27 m/s, respectively. The microstructure, wear morphology, and cross section of the worn subsurface were observed by scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) analyses were performed on the worn surfaces of Ag-Cu/MoS2 composites. The results indicated that the distribution of the MoS2 particles in the composites was improved and the interfacial strength of Ag/MoS2 was enhanced during the process of hot extrusion. The hardness, bending strength, and wear resistance of hot-extruded composites increased remarkably due to the presence of the continuous matrix skeleton and the stronger interfacial bonding of Ag/MoS2 . XPS revealed that a chemical reaction had occurred at the worn surface due to the friction heat. Although the dominant wear mechanism was fatigue wear for both the hot-pressed and hot-extruded composites, finer debris and a lower wear rate were observed in hot-extruded composites due to the fact that the nucleation and growth of cracks in the worn subsurface were restrained in the process of tribotest.